(untitled) (Praxis Educativa, 2022)
Teaching professionalism can be considered as one of the central aspects of current trends in the field of science education. This article reviews and puts into practice some central concepts of the sociocultural theory and socioconstructivism, such as the zone of proximal development and learning communities; and puts them in dialogue with the initial teacher training at the university. Based on an interpretive and idiographic approach, we conducted a design research through the planning, implementation and evaluation of teaching and learning sequences on two didactic strategies of natural sciences, implemented with a co-teaching modality and in the context of pandemic. The findings and reflections contribute to recognize the validity of guided participation in teaching (co-teaching) during initial teacher training for a specific didactic, as a transition towards the execution of teaching practices.